2020
DOI: 10.1111/dom.14242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the glucagon‐like peptide‐1 analogue liraglutide versus placebo treatment on circulating proglucagon‐derived peptides that mediate improvements in body weight, insulin secretion and action: A randomized controlled trial

Abstract: Aim To examine how circulating glucagon‐like peptide‐1 (GLP‐1) concentrations during liraglutide treatment relate to its therapeutic actions on glucose and weight, and to study the effects of liraglutide on other proglucagon‐derived peptides (PGDPs), including endogenous GLP‐1, glucagon‐like peptide‐2, glucagon, oxyntomodulin, glicentin and major proglucagon fragment, which also regulate metabolic and weight control. Materials and Methods Adults who were overweight/obese (body mass index 27‐40 kg/m2) with pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…These side effects included nausea and vomiting [26]. Likewsie, another trial conducted by Kim et al on 35 patients for 14 weeks found the similar results in terms of weight loss [27]. More precisely, authors found that subjects randomized to intervention arm (liraglutide 1.8 mg/day) were found to have a significant reduction in mean weight: -3.6% with 95% CI of -5.2% to -2.1% when compared to the placebo [27].…”
Section: Davies Etmentioning
confidence: 77%
See 1 more Smart Citation
“…These side effects included nausea and vomiting [26]. Likewsie, another trial conducted by Kim et al on 35 patients for 14 weeks found the similar results in terms of weight loss [27]. More precisely, authors found that subjects randomized to intervention arm (liraglutide 1.8 mg/day) were found to have a significant reduction in mean weight: -3.6% with 95% CI of -5.2% to -2.1% when compared to the placebo [27].…”
Section: Davies Etmentioning
confidence: 77%
“…The sample size of all included research studies varied between 9 and 564 with an equal distribution between patients who were and were not randomized to different treatment modalities under the umbrella of GLP-1 agonists in the RCTs. The studies were conducted mostly in developed countries such as USA (n = 4), Japan (n = 1, Europe (n = 1), Italy (n = 2), China (n = 2), Korea (n = 1), UK (n = 1), and Denmark (n = 1) (Table 3 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]).…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…Other potential causes of the hormonal changes could be changes in bile acids, as both CCK and FGF19 secretion is regulated by bile acids in the intestines. Finally, GLP‐1 is shown to exercise negative feedback on secretion of GLP‐1 from the L cell, this negative feedback might also affect other products from the L cell, including GLP‐2 25,26 . We cannot exclude that liraglutide‐induced weight loss may have contributed to the changes in postprandial plasma responses of CCK, GLP‐2 and FGF19 observed in the liraglutide‐treated as compared with the placebo‐treated subjects during the meal test at steady state.…”
Section: Discussionmentioning
confidence: 94%
“…It was recently identified that applying subcutaneous injections of GLP-1 receptor agonist exenatide 2 mg (ExQW) once a week and over 36 weeks leads to a reduction in the total adipose tissue waist circumference of obese individuals ( 82 ). In this context, the pharmacological manipulation of GLP-1 receptor agonists as a target in taste perception and weight loss has recently emerged ( 47 , 83 ). PYY and cholecystokinin (CCK) peptides are also related to appetite control and decreased gastric secretion ( 84 , 85 ).…”
Section: The Impact Of Obesity On the Microbiota-gut-brain Axismentioning
confidence: 99%